2013
DOI: 10.1038/srep01338
|View full text |Cite
|
Sign up to set email alerts
|

How micron-sized dust particles determine the chemistry of our Universe

Abstract: In the environments where stars and planets form, about one percent of the mass is in the form of micro-meter sized particles known as dust. However small and insignificant these dust grains may seem, they are responsible for the production of the simplest (H2) to the most complex (amino-acids) molecules observed in our Universe. Dust particles are recognized as powerful nano-factories that produce chemical species. However, the mechanism that converts species on dust to gas species remains elusive. Here we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
162
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(174 citation statements)
references
References 27 publications
11
162
1
Order By: Relevance
“…Garrod et al (2007) have previously proposed a formula in their models that can be used to describe the chemical desorption (or reactive desorption). They derived the probability of A24, page 4 of 6 Bergeron et al (2008); (c) Al-Halabi & van Dishoeck (2007), Amiaud et al (2007); (d) Pirronello et al (1997); (e) Amiaud et al (2006) for low coverage; ( f ) Minissale et al (2015); (g) Dulieu et al (2013); (h) Speedy et al (1996), Fraser et al (2001 energy derived of 5800 K with pre-factor of 10 15 s −1 here corrected to have a pre-factor of 10 12 s −1 ; (i) Noble et al (2012a); ( (2)) that include division between the degree of freedom and the fraction of kinetic energy after bounce ( is mass dependent). In red we show the equal share of energy and the constant value of .…”
Section: Theoretical Estimate Of the Desorption Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Garrod et al (2007) have previously proposed a formula in their models that can be used to describe the chemical desorption (or reactive desorption). They derived the probability of A24, page 4 of 6 Bergeron et al (2008); (c) Al-Halabi & van Dishoeck (2007), Amiaud et al (2007); (d) Pirronello et al (1997); (e) Amiaud et al (2006) for low coverage; ( f ) Minissale et al (2015); (g) Dulieu et al (2013); (h) Speedy et al (1996), Fraser et al (2001 energy derived of 5800 K with pre-factor of 10 15 s −1 here corrected to have a pre-factor of 10 12 s −1 ; (i) Noble et al (2012a); ( (2)) that include division between the degree of freedom and the fraction of kinetic energy after bounce ( is mass dependent). In red we show the equal share of energy and the constant value of .…”
Section: Theoretical Estimate Of the Desorption Efficiencymentioning
confidence: 99%
“…Coverage range indicates the coverage of molecular ice growth before atom irradiation; in the case of experiments performed only with atomic species, coverage range indicates the total amount of species placed on the surface. √ and X are used to indicate whether the experimental procedure (DED or TPD) was used or not; (#) CD decreases as a function of coverage; (&) experiments performed with excited particles (see Minissale 2014); (a) Chaabouni et al (2012); (b) Dulieu et al (2013); (c) Minissale et al (2013); (d) ; (e) ; ( * ) this work.…”
Section: Theoretical Estimate Of the Desorption Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…17 To treat reactive desorption the fraction 'f' of reactions resulting in desorption is calculated by considering the competition between the rate of desorption and the rate of energy lost to the grain: 15 (2.29) f = aP 1 + aP where a= / = 1.0 and is the ratio of surface molecule bond frequency to frequency at which energy is lost. Previous models of Nautilus use a value of .01, we use a value of 1.0 assuming reactive desorption is quite efficient at high temperatures on a bare grain in accordance with work by Dulieu et al 40 P gives the probability of desorption and is based on the Rice-Rampsberger-Kessel theory and is described in more detail in Garrod 2007:…”
Section: Desorption Processesmentioning
confidence: 99%
“…We chose this value because Dulieu et al found reactive desorption to be much more efficient in producing DO 2 on a bare graphite surface then on an icy mantle. 40 A branching ratio was assumed where a fraction 'f' of the species desorbs into the gas phase, the energy from the reaction acts to break the surface-molecule bond. In the other case this energy is lost in lateral translation along the grain surface, and 1-f stays on the grain surface.…”
Section: Desorption Processesmentioning
confidence: 99%